Estudio del rol de Galectina-1 en el establecimiento y desarrollo de la endometriosis - Bastón, Juan Ignacio (2015)
Endometriosis is characterized by the presence of endometrial tissue outside the uterus reassembled in well-vascularized endometriotic lesions. Galectin-1 (Gal-1) is an endogenous lectin upregulated in tumor and inflammatory microenvironments, where it plays essential roles in angiogenesis mechanisms. In this study, it was demonstrated that tissue expression of Gal-1 in endometriotic lesions and eutopic endometrium was restricted to stromal and endothelial cells and was absent in epithelial cells. Besides, Gal-1 protein expression levels were higher in the endometriotic lesions than eutopic endometrium from patients with minimal or mild degree of endometriosis, suggesting that Gal-1 could be playing a key role in the onset and development of this pathology at early stages. It was also found that the presence of Gal-1 is crucial for in vitro proliferation of endometrial stromal cells, for the vascular development and consequent growth of endometriotic lesions in vivo, and it was also demonstrated that the specific blockade of Gal-1 at peritoneal level restricts the growth of endometriotic lesions, suggesting that in the future this endogenous lectin could become potential therapeutic target that allows to develop new effective treatments to mitigate the progression of this disease. These results highlight the pivotal role of Gal-1 in endometriosis pathophysiology.